An Investigation into Linguistic Features of Mental Process and their Functions in the Novel "Sense and Sensibility" by Jane Austen and its Vietnamese Version - Le Thi Quyen
Chapter 1: Introduction; Chapter 2: Literature review and theoretical background; Chapter 3: Method and procedure; ...